THE RELATIONSHIP OF PARENTING PATTERNS AND LONG USE OF GADGETS WITH SOCIAL DEVELOPMENT IN PRESCHOOL CHILDREN - Ratna Dewi; Luthfianiiq Syahda Kumala; Eliana Eliana; Desi Widiyanti; Rina Rina (Poltekkes Kemenkes Bengkulu, 2022)
Social development in preschool children is needed, because it is the initial key for children to be able to live social life in the future. The social development of children at this age includes showing empathy as seen from the child's willingness to help friends who need help or showing a sense of concern by being involved in playing activities or other activities. Many factors influence the social development of children. These factors include knowledge factors, parenting patterns and duration of gadget use. Based on the results of the preliminary study, the problem of this research is that there is still a high level of social development disorders in pre-school children. This study aims to determine the relationship between parenting patterns and long use of gadgets with social development in preschool children. The design of this study used a cross sectional approach. The population of this study was 5-6 years old and a total of 66 samples were taken using a total sampling technique. Data were analyzed by univariate and bivariate. The results of this study there is a relationship between parenting patterns with social development in preschool children with p = 0.020. There is a relationship between long use of gadgets with social development in preschool children with p = 0.003. The results of the study concluded that parenting patterns and long use of of gadgets are important factors in social development in preschool children. So that parents pay attention to the importance of parenting and limit the use of gadgets in pre-school children.